The Importance Of Is’hakhan's Scientific And Creative Heritage - Bekmirzaev Mashhuru Shavkatjon qizi (Periodica Journal, 2024)
The article analyzes the significance of the scientific and creative heritage of Is’hakhan Ibrat. The questions asked in his scientific and creative heritage have been studied
Keywords: satirical works; musaddas; scientific works